The effect of leadership relationships on organizational innovativeness: comparison between bureaucratic and creative organizations - Pučėtaitė, Raminta; Novelskaitė, Aurelija; Markūnaitė, Laura (Socialiniai tyrimai, 2014)
The paper presents empirical findings of a study on the impact of leadership relationship on different forms of organizational innovativeness in bureaucratic and creative public sector organizations. The data were collected by a questionnaire survey (respectively, n=747 and n=225) in Lithuania in 2013-2014. The results of linear regression analysis indicate a tendency of a stronger effect of leadership relationship on all forms of organizational innovativeness in creative organizations.